Pemberian Kredit dengan Jaminan Fidusia pada PT Bank Mayapada Internasional Cabang Denpasar pada Masa Covid-19 - Kadek Della Ayu Saputri; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2021)
Fiduciary is one of the efficient guarantees for people who need funds amid the Covid-19 pandemic as is known the impact of this pandemic can be seen in the economic sector in Indonesia Banks are an effective intermediary institution as a channel for funds for productive financing activities which will encourage economic growth itself In this study discusses how PT Bank Mayapada Internasional Denpasar Branch provides policies in the midst of a pandemic like this then regarding the implementation of providing credit with fiduciary guarantees during the Covid-19 period as well as regarding the settlement of defaults related to providing credit with fiduciary guarantees during the Covid-19 period The type of research used is empirical legal research Based on the results of the study it is concluded that the implementation of the provision of credit during this pandemic begins with submitting a restructuring application then conducts analysis such as cash flow latest financial report checking account for the last three months collateral condition debtor s business visit and finally a new agreement is made Then the settlement of default is done by restructuring then mediation and finally by bringing the guarantee to the auction body.